Kewirausahaan Sosial dan Penciptaan Nilai Bersama: Sebuah Kajian terhadap CSR Sido Muncul untuk Program Desa Rempah dan Buah - Sirine, Hani; Andadari, Roos Kities; Suharti, Lieli (Jurnal Manajemen dan Kewirausahaan, 2020)
CSR with a shared value creation approach is characterized by the concept of social entrepreneurship, so as to produce a new business model from the social changes that occur. The purposes of this study are to determine the process of developing social entrepreneurship in the Spice and Fruit Village CSR Program and to identify the creation of shared values ​​resulting from Sido Muncul CSR program. The research method used is qualitative in which the validity of the data is tested by the triangulation method. Data collection was carried out through interviews and observations with Sido Muncul and fostered residents for the Spice and Fruit Village Program in Bergas Kidul and Diwak Villages. The results of this study indicate that the process of developing social entrepreneurship in CSR programs is carried out through several stages, including identification of social problems, allocation of resources, collaboration and partnerships, adaptation of products and processes, and social innovation. The creation of shared values ​​resulting from the CSR program is organizational performance and social performance. Organizational performance can be seen through management support, employee commitment, company reputation, and organizational finance. Social performance can be seen through the role of social entrepreneurship, harmonious relationships between shareholders and stakeholders, social innovation, and community independence. Organizational performance has a reciprocal relationship with social performance, which can produce sustainable growth.https://doi.org/10.26905/jmdk.v8i2.4240